Synthetic Studies on an Antitumor Antibiotic, Bleomycin. XII. Preparation of an L-2, 3-Diaminopropionic Acid Derivative as a Synthetic Intermediate - YAMASHITA, HARUO; KITTAKA, ATSUSHI; IIMORI, TAKAMASA; OTSUKA, MASAMI; OHNO, MASAJI; KOBAYASHI, SUSUMU (Chemical & pharmaceutical bulletin, 1985)
Three methods have been developed for the preparation of (S)-3-amino-2-tert-butoxycar-bonylaminopropionamide suitably protected for use in the total synthesis of bleomycin.